Implications for Paleontological Heritage Conservation: The Spatial Distribution and Potential Factors Controlling the Location of Fossil Sites of Shandong Province in China - Ying Guo; Yu Sun; Xiaoying Han; Yan Zhao; Song Zhou; Yachun Zhou; Tian He; Yingming Yang (Applied Sciences)
Shandong Province in China is rich in paleontological fossils and has a long history of fossil research. However, research on the distribution characteristics and potential factors of discovered fossil sites in Shandong Province is limited and insufficient, making it difficult to comprehensively plan for the protection and utilization of fossil sites in Shandong Province. The study constructs a basic geographical information system (GIS) database with 133 discovered fossil sites and geological and socio-economic data of Shandong Province and studies fossil sites’ spatial distribution characteristics and the spatial relationship with potential factors at a regional scale. The results are as follows: (1) The fossil sites in Shandong Province are concentrated in the mountainous area of central Shandong and the hilly area of the Shandong Peninsula, with significant uneven distribution characteristics, including two agglomeration areas and seven sub-agglomeration areas. (2) Natural geographical conditions, such as topography, paleogeography, and stratigraphy, play a positive role in the distribution of fossil sites, and there are apparent concentrations in the following areas: at an altitude greater than 100 m; the Lower Paleozoic and Cretaceous sedimentary rocks; and the active areas of paleo-tectonics. (3) A certain degree of negative correlation exists between socio-economic conditions, such as roads and population density, and the number of fossil sites, and a positive correlation exists between disposable personal income and those fossil sites. The operational procedure presented here is a simple, objective, applicable method that can enhance our understanding of the spatial distribution patterns and influencing factors of the discovered fossil sites of Shandong Province and support more effective and appropriate planning for paleontological heritage conservation.